Evaluierung der Ub̈ergangsregelung des Herkunftsschutzes bei Agrarprodukten und Lebensmitteln in Europa gemas̈s Verordnung (EG) Nr. 510/06 und Verbesserungsvorschlag̈e fur̈ die anstehende Modifikation - Adriano Profeta; Richard Balling (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2007)
– With the coming-into-effect of regulation (EC) Nr. 510/06 from the 20th March 2006 and the executive regulation (EG) Nr. 1898/06 the community-wide protection of geographical indications and designations of origin for agricultural products and foods received a new legal basis. The new regulation replaces the old regulation (EG) Nr. 2081/92. Because some of the changes have great significance for new applications of producer groups and for their communication policy in this paper the most important modifications will be presented and evaluated. Furthermore proposals for possible future modifications are discussed.
Keywords: 330; Herkunftsbezeichnung; Agrarprodukt; Lebensmittel; EU-Staaten